Influence of diet on the gut microbiota - Justyna Dąbrowska; Magdalena Wójcik; Grzegorz Boreński; Damian Bator; Joanna Milanowska (Kazimierz Wielki University, 2020)
Introduction: Gut microbiota is still a new direction in medicine. The intestinal microbiota contains up to 100 trillion bacteria and around 1000 species. The composition of the intestinal microflora may be affected by external factors, among which eating habits can be considered as one of the most important. There are evidences how gut microbiota may affect the course of diseases, such as autism spectrium disorders, mood disorders, celiac disease, irritable bowel syndrome, diabetes and colorectal cancer The aim of the study: The purpose of this systemic review was to collect and analyse current and new informations on the effect of diet on intestinal microbiota. Material and method: Standard criteria were used to review the literature data. The search of articles in the PubMed database was carried out using the following keywords: microbiota, gut, diet, gluten-free-diet, ketogenic-diet. Description of the state of knowledge: There are many studies that show the effect of diet on the intestinal microflora. Changing the amount of plant fiber consumed, ketogenic diet, gluten-free diet can affect the composition of the intestinal microflora in various ways, as shown by the evidence presented by us. For instance ketogenic diet in patients with refractory epilepsy may reduce the symptoms of the disease, which is associated with changes in the composition of gut microbiota. Summary: Diet is a promising direction of development, due to being a  factor which may improve the course of many diseases.  However, despite the fact that many new studies have appeared in this field in the last decade, time is still needed to draw specific conclusions.